160 dB dynamic range pixel with charge compensation for CMOS image sensor. Issue 10 (1st May 2016) - Li, Zhaohan; Wang, Xinyang; Li, Bing; Chang, Yuchun
Abstract : A 160 dB high dynamic range pixel architecture with charge compensation technique for CMOS image sensor (CIS) is presented. Employing a built‐in charge compensation photodiode, the operation mode of the proposed pixel can switch between linear mode and logarithmic mode automatically according to the incident light intensity. The measured result shows a CIS with the proposed pixel architecture has a dynamic range up to 160.9 dB with an output swing of 1.9 V. Moreover, this scheme does not require complex control circuits and complicated timing sequence.